Cdc42 induces EGF receptor protein accumulation and promotes EGF receptor nuclear transport and cellular transformation. Issue 2 (10th December 2014) - Wang, Xiao-Yu; Gan, Ming-Xi; Li, Yong; Zhan, Wei-Hua; Han, Tian-Yu; Han, Xiao-Jian; Cheng, Jin-Quan; Wang, Jian-Bin
Abstract : Cdc42 is a Ras‐related small GTP‐binding protein. A previous study has shown that Cdc42 binding to the γ subunit of the coatomer protein complex (γCOP) is essential for Cdc42‐regulated cellular transformation, but the molecular mechanism involved is not well understood. Here, we demonstrate that constitutively‐active Cdc42 binding to γCOP induced the accumulation of epithelial growth factor receptor (EGFR) in the cells, sustained EGF‐stimulated extracellular signal‐regulated kinase (ERK), JUN amino‐terminal kinase (JNK) and phosphoinositide 3‐kinase (PI3K) signaling and promoted cell division. Moreover, constitutive Cdc42 activity facilitated the nuclear translocation of EGFR, and this indicates a novel mechanism through which Cdc42 might promote cellular transformation. Abstract : Disrupting the interaction between actived Cdc42 and γCOP down‐regulates EGFR level. Nuclear accumulation of EGFR in cells stably expressing constitutively active. Cdc42 associates with sustained MAPK‐PI3K activity and transformed phenotypes.